Simultaneous Trapping of C2H2 and C2H6 from a Ternary Mixture of C2H2/C2H4/C2H6 in a Robust Metal–Organic Framework for the Purification of C2H4. Issue 49 (11th November 2018) - Hao, Hong‐Guo; Zhao, Yun‐Feng; Chen, Di‐Ming; Yu, Jia‐Mei; Tan, Kui; Ma, Shengqian; Chabal, Yves; Zhang, Zhi‐Ming; Dou, Jian‐Min; Xiao, Zi‐Hui; Day, Gregory; Zhou, Hong‐Cai; et al.
Abstract: The removal of C2 H2 and C2 H6 from C2 H4 streams is of great significance for feedstock purification to produce polyethylene and other commodity chemicals but the simultaneous adsorption of C2 H6 and C2 H2 over C2 H4 from a ternary mixture has never been realized. Herein, a robust metal–organic framework, TJT‐100, was designed and synthesized, which demonstrates remarkably selective adsorption of C2 H2 and C2 H6 over C2 H4 . Breakthrough experiments show that TJT‐100 can be used as an adsorbent for high‐performance purification of C2 H4 from a ternary mixture of C2 H2 /C2 H4 /C2 H6 (0.5:99:0.5) to afford a C2 H4 purity greater than 99.997 %, beyond that required for ethylene polymerization. Computational studies reveal that the uncoordinated carboxylate oxygen atoms and coordinated water molecules pointing towards the pore can trap C2 H2 and C2 H6 through the formation of multiple C−H⋅⋅⋅O electrostatic interactions, while the corresponding C2 H4 –framework interaction is unfavorable. Abstract : A robust porous metal–organic framework was synthesized and utilized for the highly selective separation of C2 H4 from a ternary mixture of C2 hydrocarbons. After a single operation, the C2 H4 purity of the outlet was greater than 99.997 %.